Unsettling White Settler Child and Youth Care Pedagogy and Practice: Discourses on Working in Colonial Violence and Racism - MacKenzie, Kaz (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
In 2018, using in-depth, semi-structured, collaborative dialogues, I asked 11 child and youth care practitioners working in various Canadian provinces, including British Columbia, Alberta, and Ontario, “How do you understand, name, reproduce, contest, and struggle with White settler privilege?” The intent was to name and challenge the dominant Whitestream norms in child and youth care. This project was inspired by the significant work of Indigenous and racialized activist–scholars to address the ongoing overrepresentation of Indigenous families across colonial systems in which child and youth care practitioners work, such as the child welfare and justice systems, and the underrepresentation in others, such as educational systems. Participants named colonial violence and systemic racism as entrenched in child and youth care practice while recognizing the difficulty of challenging dominant White norms and conventions in the classroom and field. I explore how this key finding unsettles child and youth care pedagogy and practice. In closing, I propose two practical ethical pathways towards unsettling White settler privilege in child and youth care.